Measurement and modelling of temperature-dependent thermal diffusivity of diamond films - Hui, Ping. (2008)
First paper shows how the transmission-line theory is applied for obtaining thermal solutions for 2 and 3-layer samples, and investigate on how different pulse shapes affect the curve fitting results. Second paper investigates how gold film’s thermal conductivity varies with different kind of substrates. Third paper presents a rigorous analytical series solution of temperature distributions in a circularly cylindrical diamond heat spreader with temperature-dependent diamond thermal conductivity.